Correction: Study assessing the effectiveness of overdose prevention centers through evaluation research (SAFER): an overview of the study protocol. - Cerdá, Magdalena.; Allen, Bennett L; Collins, Alexandra B; Behrends, Czarina N; Santacatterina, Michele.; Jent, Victoria.; Marshall, Brandon D (Tufts University. Tisch Library., 2025)
Springer Open.